Recent Trends in Cardiovascular Risks - Kumar, Arun (IntechOpen, 2017)
Salient features of the book: - All chapters are related to the advances in cardiovascular risks.; - Chapters are written by renowned authors globally. - Chapters are lucid and easy to understand. - Chapters are useful for clinicians, medical practitioners, researchers, teachers, and students. - Chapters include flow charts, diagrams, and tables for easy comprehension of overall risks of cardiovascular disease. - Chapters generate awareness among common people about the risks so that the cost of intensive care units can be prevented, thus the economy of the country.